Bulgarian weightlifters women' achievements at European Championsips and analysis of medalists' sports profile - Yankova, N. (Research in Kinesiology, 2017)
The aim of the study is to analyze the rankings of Bulgarian women weightlifters at European Weightlifting Championships and describe medalists`personal profiles by the dynamics of their sports performance. The report analyzes the rankings of Bulgarian weightlifters women at European Championshipsand medalists` personal profiles through dynamics of athletic performance by Sinclair` coefficientfor the period 1988 -2016. Based on the analysis it hasbeen established thenumber of competitors won medals and titles who have hada long successful sportscareer. Personal and summarized analysis for sports performance has been made that showed a growth of over 30 according to Sinclair` coefficient. Object ofthe study: Bulgarian women weightlifters medalists from European Championships in age group 17 to 33. The results of weightlifters prove that physical exercisesaffect humans` physiological functions, but adaptative capabilities of the body allows overcoming the accompanying troubles and achieving success atthe championships. It was also found that high sports performancein weightlifting has no negative affection to the motherhood` functionof women competitors and it is not an obstacle for achieveing high sports results.